ANALYSIS OF ACCOUNTING TREATMENT OF CAPITAL EXPENDITURE AND REVENUE EXPENDITURE - Kalsum, Umi (International Proceeding of Law and Economic; 2020: International Proceeding of Law and Economic, 2021)
Management of PT. Pelindo I (Persero) Belawan Branch should use records in accordance with applicable accounting standards. An asset can be said to be revenue expenditure if it has a useful life of less than one accounting period and has a relatively small acquisition price. The accounting treatment of capital expenditure and revenue expenditure is in accordance with PSAK No. 16. except for the recording is not in accordance with the applicable accounting standards. Management of PT. Pelindo I (Persero) Belawan Branch should use records in accordance with applicable accounting standards. An asset can be said to be revenue expenditure if it has a useful life of less than one accounting period and has a relatively small acquisition price. The accounting treatment of capital expenditure and revenue expenditure is in accordance with PSAK No. 16. except for the recording is not in accordance with the applicable accounting standards. Management of PT. Pelindo I (Persero) Belawan Branch should use records in accordance with applicable accounting standards.